2017
DOI: 10.11157/anzswj-vol29iss3id254
|View full text |Cite
|
Sign up to set email alerts
|

Zooming in: Social work supervisors using online supervision

Abstract: A group of geographically dispersed social work practitioners who provide professional supervision responded to an invitation put out through the Aotearoa New Zealand Association of Social Workers (ANZASW) networks to be part of an online group in late 2015. Seven members committed to meeting for one hour every eight weeks using the online meeting platform, ZoomTM. This viewpoint provides an opportunity to share our experience of the development and process of this group, with its potential for ensuring a safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Therefore, CAS is proved to be very useful for postgraduate research supervision (Nordentoft et al, 2013), which has faced many challenges, such as the decreasing supervisor‐student ratio and the increasing pressure for timely completion and active supervision (McCallin & Nayar, 2012). CAS has been implemented to tackle these challenges (e.g., Wichmann‐Hansen et al, 2015; Boud & Lee, 2005), as it encourages peer feedback in addition to supervisor's feedback (Wisker et al, 2007; Rushton et al, 2017) and aims to promote students' academic participation and research capacity (Fenge, 2012). Stracke (2010), for instance, set up peer group meetings in a doctoral programme, with the supervisor playing a moderator's role.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, CAS is proved to be very useful for postgraduate research supervision (Nordentoft et al, 2013), which has faced many challenges, such as the decreasing supervisor‐student ratio and the increasing pressure for timely completion and active supervision (McCallin & Nayar, 2012). CAS has been implemented to tackle these challenges (e.g., Wichmann‐Hansen et al, 2015; Boud & Lee, 2005), as it encourages peer feedback in addition to supervisor's feedback (Wisker et al, 2007; Rushton et al, 2017) and aims to promote students' academic participation and research capacity (Fenge, 2012). Stracke (2010), for instance, set up peer group meetings in a doctoral programme, with the supervisor playing a moderator's role.…”
Section: Introductionmentioning
confidence: 99%
“…They prepare a draft report and a PowerPoint presentation on their findings. (MacKeogh, 2006, p. 21)The component of peer supervision extends the traditional supervisor–supervisee dyad to meet the supervisory and learning needs of a particular group (Rushton et al, 2017). MacKeogh's (2006) analysis of the peer interactions on Moodle showed that peer feedback covered topic selection, answering questions on statistics, advising on methods or references, and helping to find participants or distribute questionnaires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation